Analysis of the fracture behavior of polypropylene: sawdust composites - João C. Miguez Suarez; Fernanda M. B. Coutinho; Thais H. Sydenstricker (Polímeros, 2005)
Natural fiber reinforced composite is an emerging area in Polymer science. The use of lignocellulosic materials in thermoplastic composites may contribute to reduce the waste of vegetal biomass. The natural fibers are biodegradable, low cost materials having density and specific properties comparable to those of conventional fiber composites. In this work composites of polypropylene (PP) plus maleated polypropylene (MAPP) filled with sawdust were prepared under fixed processing conditions (mixing temperature, mixing time and rate of rotation). The composites were fractured by tension and the fracture mechanisms were characterized by scanning electron microscopy. The SEM studies of the fractured surfaces of the composites indicate that the failure is due to fiber pull-out accompanied by tearing of the matrix; the pull-out increases with MAPP content.